An Analysis Of Grammatical Errors Made By English Education Students In Writing Instagram Captions - Ginting, Dwi Prisilla Br; Pakpahan, Carolina; Girsang, Susanti (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This research aims to analyze grammatical errors found in Instagram captions written by English Education students of HKBP Nommensen University Medan. The objectives of this study are to identify the types of grammatical errors, determine the most dominant error, and analyze the factors that cause these errors. This research used a qualitative descriptive method. The data consisted of 50 Instagram captions collected from students’ Instagram accounts through documentation techniques. The data were analyzed using the Surface Strategy Taxonomy proposed by Dulay, Burt, and Krashen (1982), which classifies grammatical errors into four types: omission, addition, misformation, and misordering. The results of the research show that all four types of grammatical errors were found in the students’ Instagram captions. Among the errors, omission was the most dominant type, occurring 21 times or 42% of the total errors. Misformation occurred 17 times, addition occurred 8 times, and misordering occurred 4 times. These findings indicate that students still face difficulties in applying correct grammatical structures when writing captions in English. Furthermore, the study revealed that grammatical errors were mainly caused by three factors: interlingual transfer, intralingual transfer, and overgeneralization. Therefore, it can be concluded that students need to improve their understanding of English grammar to reduce grammatical errors not only in academic writing but also in everyday communication on social media.